Arsenic and Mercury Concentrations at Several Geothermal Systems in West Java, Indonesia - N. R. Herdianita; B. Priadi (Journal of Mathematical and Fundamental Sciences, 2008)
A study at several geothermal systems in West Java, Indonesia shows that thermal waters could naturally contain up to 2.6 ppm As and 6.5 ppb Hg, and the surface hydrothermal alteration could contribute up to 50 ppm As and 800 ppb Hg. The higher the chloride content, the higher the contents of As and Hg of thermal waters. The amounts of As and Hg in an active geothermal system are influenced by the type of host rock, boiling and mixing processes, and adsorption of vapor and volcanic gases into thermal waters.